O fenômeno das marés : gravitação e astronomia numa proposta de unidade de ensino potencialmente significativa para o ensino médio - Silva, Francisco Paiva da (2016)
The paper reports the development,  implementation and evaluation of a Potentially Meaningful Teaching Unit (PMTU) about the tides phenomenon targeted to high school, which relates the tides phenomenon with Gravitation and Astronomy. Were held 14 activities such as drawings and questionnaire, aiming to survey the initial conceptions, reading and discussion of texts, content presentation for slides, simulation activity phases of the moon using the body, discussion and activities of reworking, presentation activities to the large group and press conference. They participated in the development of this work 21 students the first year of high school of E.E.E.F.M. Ewerton Montenegro Guimarães, a school of public schools, located in Viana district, ES. The PMTU was evaluated throughout their development process and the end, together with the students through a news conference. The materials and tools that were the basis for data collection and results analysis were drawings and quizzes, videos and activities of the press conference, audio lessons, plus a daily implementation. The students demonstrated a high degree of involvement in some activities, many questions regarding the content of study and a lot of willingness to carry out practical activities, but very difficult to read and little envolvement in expository activities. From the results obtained throughout the process of implementation of PMTU, it was revealed few significant learning of evidence indicating that the goal of PMTU seems to have been reached, but it is possible to realize an increase of knowledge and possible conceptual evolution. With this work it was also possible to know a little more about teaching and learning, to make an analysis of the teaching practice itself and to acquire experience in order to improve product that can serve as a reference to other teachers who wish to develop similar education projects addressing tides, gravitation and astronomy.